Approach Model Driven Engineering: Profiling Group Collaborative Learner in Mobile Learning - Razanakolona, Livaniaina; Razafimandimby, Josvah Paul; H.C.C., Andriamiandanomenajanahry; Rhazali, Yassine (Procedia computer science, 2020)
Model Driven Engineering (MDE) has shown its results in the software development, particularly with the Model Driven Architecture approach (MDA). While the learner group specification phase, to perform collaborative activities in an integrated Technology Enhanced Learning (TEL) embedded system, is in-depth. Our proposal is based on the model driven engineering in the context of learner profile. Our hypothesis is the clustering analysis and then the use of models extracted from the group profile during collaborative mobile learning (m-Learning). These extracted models are at the heart of the approach we propose and which is the subject of this paper.